Pour un retour des biens communs fonciers ? - David Goeury (Belgeo)
In Morocco, commons pool resources originate cultural and ecological heritage. However, following colonization, they have been either state-controlled or privatized. The historical owners’ communities have not disappeared and remain mobilized around resources which they consider to have been unjustly dispossessed. The return of commons pool resources seems to be linked to evocation of an idyllic past. They are seen as singular governance and collective democracy, opposed to the authoritarianism and corruption of contemporary administrations. Their revival is achieved through new local committees, but can only be perpetuated by the benevolence of national political institutions, and particularly of municipal authority. However, the temptation to limit this heritage to its landscape hides civic foundation articulated around the involvement to do together as citizenship praxis.